Characterization of the University of Bohol Ecofarm: An Urban Forestry Development Model - Bullecer, Ricardo P. (JPAIR Multidisciplinary Research, 2010)
Urban forestry advocates the role of trees as a critical part of the urban infrastructure. Establishment of higher vegetation is highly called for in improving the health of the environment and the community especially in these days when the effects of global warming is obviously felt everywhere, much more in urban areas. Among the vast resources of the University of Bohol is a 2.1-hectare lot in Village San Isidto, Tagbilraran City which has commonly been referred to as the "UB Ecofarm". The site is a degraded karst land which has been left idle for quite some time with indigenous pioneer species and other dominant scrubby vegetation. A survey was then conducted to gather baseline information on the existing floral and faunal resources as well as edaphic and geo factors characterizing the area. The creation of an urban forestry development plan was the ultimate purpose and output of this research endeavor. Despite the degraded condition of the site, results showed a total of 65 species of trees and shrubs, 56 species of grasses and broadleaved weeds; 25 bird species, 4 bat species and others like frogs and rodents. The stunted vegetation is growing in patches. Timber poaching, wildlife hunting and unauthorized pasturing of animals are the major problems in the site. The area has the potential for a bird sanctuary, a demo area of a sub-urban vegetation rehabilitation, organic farming in selected spots and a biodiversity conservation center for the city